Effects of natural and anthropogenic drivers on land‐cover change and treeline dynamics in the Apennines (Italy). (24th January 2018) - Vitali, Alessandro; Urbinati, Carlo; Weisberg, Peter J.; Urza, Alexandra K.; Garbarino, Matteo
Abstract: Questions: How do climate, topography and human impact affect land‐cover changes, elevation of treelines and dominant tree species composition at multiple spatial scales? Location: Apennine Mountains, Italy. Methods: At the regional scale ( n = 776 municipalities covering 43, 000 km 2 ), we assessed the relationship between human demographic processes and forest cover dynamics for the 1990–2012 period using Corine Land Cover maps and a national census data set. At the landscape scale ( n = 18 landscape units of 16 km 2 each), we tested the effects of site topography on forest cover changes between 1954 and 2012. At the local scale ( n = 5, 484 sampling points), we extracted the location and species composition of the current treeline (year 2012) using semi‐automatic segmentation methods. We quantified the association of climatic, topographic and anthropogenic variables with the position of upper treelines in the Apennines. Results: Regional scale: human population in the Apennines decreased by 3% between 1991 and 2011. During the same time period, there was an increase in the extent of shrublands (+7%) and forests (mixed +4%, conifers +2%, broad‐leaf +1%) and a decrease in the extent of pastures (−9%). Landscape scale: forests expanded more on southwest (+109%) than on northeast (+19%) slopes. Local scale: the mean treeline altitude was 1, 755 m a.s.l. Fagus sylvatica L. was the most widespread species (94%), but we also found Pinus nigra Arn. plantations and Pinus mugo Turra shrublands in the central Apennines, and Pinus heldreichii H.Christ in the southern Apennines. Overall, the elevations of the current treelines are negatively related to population density, road proximity and southwest exposures, especially among P. nigra stands. Conclusions: At the regional scale, demographic and land‐cover changes provide evidence of widespread land abandonment and forest expansion. At the landscape scale, secondary succession occurred particularly at sites with more solar radiation (SW slopes) and a previous heavier human footprint, followed by a widespread abandonment. Treelines of the dominant tree species ( F. sylvatica ) were found at elevations lower than would be predicted based on climate conditions alone, suggesting a widespread and strong role of past human influence on the location of treelines. The altitudinal transition from broad‐leaf to conifer species does not generally occur here, as would be expected from a global ecological model. Anthropogenic treelines of the Apennines will react differently than natural climatic treelines to global environmental changes. Models of treeline response to global change in the Mediterranean area should account for land‐use history. Abstract : Multiscale approach is an excellent tool to detect the recent dynamics of Mediterranean anthropogenic treelines. Along the Apennines man lowered treeline elevation and constrained forest species composition. Beech is the dominant species and the altitudinal transition broadleaf‐conifer species does not generally occur. Apennine treelines will react differently to global environmental changes than climatic ones requiring the analysis of land‐use history.